Follitropin delta combined with menotropin in patients at risk for poor ovarian response during in vitro fertilization cycles: a prospective controlled clinical study - Oscar Barbosa Duarte-Filho; Eduardo Hideki Miyadahira; Larissa Matsumoto; Lucas Yugo Shiguehara Yamakami; Renato Bussadori Tomioka; Sergio Podgaec (BMC, 2024)
Abstract Background The maximum daily dose of follitropin delta for ovarian stimulation in the first in vitro fertilization cycle is 12 μg (180 IU), according to the algorithm developed by the manufacturer, and based on patient's ovarian reserve and weight. This study aimed to assess whether 150 IU of menotropin combined with follitropin delta improves the response to stimulation in women with serum antimullerian hormone levels less than 2.1 ng/mL. Methods This study involved a prospective intervention group of 44 women who received 12 μg of follitropin delta combined with 150 IU of menotropin from the beginning of stimulation and a retrospective control group of 297 women who received 12 μg of follitropin delta alone during the phase 3 study of this drug. The inclusion and exclusion criteria and other treatment and follow-up protocols in the two groups were similar. The pituitary suppression was achieved by administering a gonadotropin-releasing hormone (GnRH) antagonist. Ovulation triggering with human chorionic gonadotropin or GnRH agonist and the option of transferring fresh embryos or using freeze-all strategy were made according to the risk of developing ovarian hyperstimulation syndrome. Results Women who received follitropin delta combined with menotropin had higher estradiol levels on trigger day (2150 pg/mL vs. 1373 pg/mL, p < 0.001), more blastocysts (3.1 vs. 2.4, p = 0.003) and more top-quality blastocysts (1.8 vs. 1.3, p = 0.017). No difference was observed in pregnancy, implantation, miscarriage, and live birth rates after the first embryo transfer. The incidence of ovarian hyperstimulation syndrome did not differ between the groups. However, preventive measures for the syndrome were more frequent in the group using both drugs than in the control group (13.6% vs. 0.6%, p < 0.001). Conclusions In women with serum antimullerian hormone levels less than 2.1 ng/mL, the administration of 150 IU of menotropin combined with 12 μg of follitropin delta improved the ovarian response, making it a valid therapeutic option in situations where ovulation triggering with a GnRH agonist and freeze-all embryos strategy can be used routinely. Trial registration U1111-1247-3260 (Brazilian Register of Clinical Trials, available at https://ensaiosclinicos.gov.br/rg/RBR-2kmyfm ).